2022
DOI: 10.1039/d2ta07353f
|View full text |Cite
|
Sign up to set email alerts
|

A solar-powered interfacial evaporation system based on MoS2-decorated magnetic phase-change microcapsules for sustainable seawater desalination

Abstract: A novel solar-powered interfacial evaporator based on the MoS2-decorated magnetic phase change microcapsules (hereafter named "MoS2-MEPCM") has been developed for sustainable seawater desalination. The MoS2-MEPCM was synthesized through encapsulating n-docosane...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…[1][2][3][4] Currently, solar-driven interfacial desalination has emerged as a promising technique to increase potable water supplies due to the abundant and sustainable solar energy. [5][6][7][8] Over the past decades, evaporation performance has been optimized by improving optical absorption, [9][10][11][12][13][14] minimizing heat loss, 15 reducing the evaporation enthalpy, 16,17 latent heat utilization [18][19][20] as well as quick water collection. [21][22][23] Unfortunately, salt deposits emerge at the evaporating surface in longterm desalination, particularly for high-salinity brine, causing reduced light absorption and inefficient water transport.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Currently, solar-driven interfacial desalination has emerged as a promising technique to increase potable water supplies due to the abundant and sustainable solar energy. [5][6][7][8] Over the past decades, evaporation performance has been optimized by improving optical absorption, [9][10][11][12][13][14] minimizing heat loss, 15 reducing the evaporation enthalpy, 16,17 latent heat utilization [18][19][20] as well as quick water collection. [21][22][23] Unfortunately, salt deposits emerge at the evaporating surface in longterm desalination, particularly for high-salinity brine, causing reduced light absorption and inefficient water transport.…”
Section: Introductionmentioning
confidence: 99%
“…Sheng et al developed a bamboo-based solar evaporator that combined Pd and Ag nanoparticles with natural bamboo . Shen et al used MoS 2 /MEPCM as a photothermal material, aerogel blanket as a heat barrier, and water pumps as a water transporter to design a solar evaporation device that exhibited a high evaporation rate of 2.06 kg m –2 h –1 under 1 sun illumination . Zhu et al reported a solar evaporator that combined fine metal nanoparticles with natural wood.…”
Section: Introductionmentioning
confidence: 99%
“…To date, various core–shell structured photothermal materials have been extensively investigated for several applications such as phase-change materials, antibacterial agents, and tumor therapies . A few recent studies on interfacial evaporators, based on magnetic phase-change microcapsules, where the phase-change material as a core is enveloped by a solar absorber-coated magnetic composite shell, have further underscored the potential of core–shell heterostructures in enhancing photothermal effects. – Nevertheless, the exploitation of the improved photothermal effect originating from the core–shell structure to facilitate the interfacial water evaporation process has yet to be fully examined. In addition, the mechanism driving the elevated heat generation in the core–shell structure has seldom been studied.…”
Section: Introductionmentioning
confidence: 99%